Waste to wealth : Collagen from fish scales - Srinivasan, Arthi; gupta, Arun (2021)
Fish Collagen is a functional molecule that can be modified and developed in different forms and can be used in various fields, from food, cosmetics to biomedical and regenerative medicine. Collagen has earned a spot in the age of advanced materials due to their properties: bioavailability, biocompatibility,weak antigenicity and the similarity to inorganic polymers.